Global profiling of lncRNAs-miRNAs-mRNAs reveals differential expression of coding genes and non-coding RNAs in the lung of beagle dogs at different stages of Toxocara canis infection. Issue 1 (January 2021) - Zheng, Wen-Bin; Zou, Yang; He, Jun-Jun; Elsheikha, Hany M.; Liu, Guo-Hua; Hu, Min-Hua; Wang, Shui-Lian; Zhu, Xing-Quan
Graphical abstract: Highlights: Global profiles of lncRNAs-miRNAs-mRNAs in the lungs of Beagle dogs infected with Toxocara canis were determined. Many altered RNAs were found in infected dogs, but the inflammatory responses remained balanced. The level of scgb1a1 increased more than 100 times in the three stages of infection. The competing endogenous RNA networks of DElncRNA-DEmiRNA-DEmRNA were constructed. New insights into the interaction between T. canis and the canine lung were provided. Abstract: The roundworm Toxocara canis causes toxocariasis in dogs and larval migrans in humans. Better understanding of the lung response to T. canis infection could explain why T. canis must migrate to and undergoes part of its development inside the lung of the definitive host. In this study, we profiled the expression patterns of long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and mRNAs in the lungs of Beagle dogs infected by T. canis, using high throughput RNA sequencing. At 24 h p.i., 1, 012 lncRNAs, 393 mRNAs and 10 miRNAs were differentially expressed (DE). We also identified 883 DElncRNAs, 264 DEmRNAs and 20 DEmiRNAs at 96 h p.i., and 996 DElncRNAs, 342 DEmRNAs and eight DEmiRNAs at 36 days p.i., between infected and control dogs. Significant changes in the levels of expression of transcripts related to immune response and inflammation were associated with the antiparasitic response of the lung to T. canis . The remarkable increase in the expression of scgb1a1 at all time points after infection suggests the need for consistent moderation of the excessive inflammatory response. Also, upregulation of foxj1 at 24 h p.i., and downregulation of IL-1β and IL-21 at 96 h p.i., suggest an attenuation of the humoral immunity of infected dogs. These results indicate that T. canis pathogenesis in the lung is mediated through contributions from both pro-inflammatory and anti-inflammatory mechanisms. Competing endogenous RNA (ceRNA) network analysis revealed significant interactions between DElncRNAs, DEmiRNAs and DEmRNAs, and improved our understanding of the ceRNA regulatory mechanisms in the context of T. canis infection. These data provide comprehensive understanding of the regulatory networks that govern the lung response to T. canis infection and reveal new mechanistic insights into the interaction between the host and parasite during the course of T. canis infection in the canine.